Self-Criticism and Emotional Numbness: The Mediating Role of Self-Alienation - Benali, Youssef; Hernández, Carlos; Novak, Mateja (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate whether self-alienation mediates the relationship between self-criticism and emotional numbness among adults. Methods and Materials: A descriptive correlational design was employed with a sample of 415 adults from Mexico, selected based on the Krejcie and Morgan sample size table. Participants completed standardized self-report measures assessing self-criticism, self-alienation, and emotional numbness. Data were analyzed using SPSS-27 for descriptive and inferential statistics, including Pearson correlation, and AMOS-21 for Structural Equation Modeling (SEM). Assumptions of normality, linearity, and multicollinearity were tested and confirmed prior to analysis. Findings: Pearson correlation results indicated significant positive associations between self-criticism and emotional numbness (r = .47, p < .001), self-criticism and self-alienation (r = .58, p < .001), and self-alienation and emotional numbness (r = .61, p < .001). The SEM analysis demonstrated acceptable model fit indices (χ²/df = 2.35, GFI = 0.95, CFI = 0.96, RMSEA = 0.057). Direct effects were significant for self-criticism on emotional numbness (β = .32, p < .001), self-criticism on self-alienation (β = .51, p < .001), and self-alienation on emotional numbness (β = .43, p < .001). The indirect effect of self-criticism on emotional numbness via self-alienation was also significant (β = .22, p < .001), confirming the partial mediating role of self-alienation. Conclusion: The findings underscore the critical role of self-alienation as a mediating mechanism between self-criticism and emotional numbness. These results highlight the importance of addressing internal disconnection in interventions aimed at reducing affective disengagement in self-critical individuals. Targeting both self-criticism and self-alienation may enhance emotional re-engagement and psychological well-being.